Infrared spectroscopy characteristics of mount Sinabung volcanic materials, North Sumatra, Indonesia. (November 2019) - Zaini, N; Irwandi, I; Abdullah, F; Meer, F van der
Abstract: Infrared spectroscopy has the capability to determine the mineralogical composition of geologic materials. Its reflectance spectra contain diagnostic spectral absorption feature characteristics that can be used for analyzing the mineral chemistry and chemical composition of volcanic material samples. In this research, we analyze the infrared spectral shapes and properties of volcanic materials at specific wavelength ranges in order to identify compositional information of the samples. We used volcanic material samples such as ash and rocks (tuffs) collected from Sinabung volcano, North Sumatra, Indonesia. Reflectance spectra of the samples were characterized using infrared spectroscopic method. Variation in depth of spectral absorption features and reflectance values of ash and rock samples related to grain size, chemical and mineralogical composition, and surface roughness of the samples. The spectroscopic characteristics showed that these volcanic samples exhibit a strong Al-OH absorption feature centered at ~2200 nm. It indicates that the samples contain predominantly clay or other phyllosilicate minerals. Reflectance spectroscopy can be used to extract compositional information of mineralogy in volcanic material samples.